Parallelizable cipher of color image based on two-dimensional chaotic system - Sawsen Abdulhadi Mahmood; Khalid Ali Hussein; Yaseen Naser Jurn; Ekhlas Abbas Albahrani (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper aims to present a parallel implementation based color image encryption using non -linear chaotic system. The adopted chaotic system was suggested and approved in our previous work [1] which generates key streams with chaotic behavior. In this paper, pixel level permutation algorithm based on chaotic map generation is investigated and analyzed. The encryption–decryption schemes are achieved in parallel and composed of three main phases: chaotic keys generation, pixel-level permutation and bit-level diffusion phase. Both permutation and diffusion processes are achieved according to the chaotic keys. The parallel implementation of the proposed image encryption system is realized and inspired with parallel computing library offered by Matlab 2018, which equips highly performance than the pipeline ones and would be helpful to utilize in image encryption/decryption for real time application. Security and statistical analysis in addition to the main differential attacks analysis are specified to evaluate the performance of the proposed image encryption algorithm with parallel implementation. From the experimental results, the output image of the encryption task shows a higher randomness of the encrypted image which can be effectively resistant to attacker. Furthermore, the run time of encryption process is faster than other research works.